1999
DOI: 10.1007/s002590050434
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high-energy photons on the spectrum of iodine-123 with low- and medium-energy collimators: consequences for imaging with 123 I-labelled compounds in clinical practice

Abstract: Using iodine-123 labelled radiotracers, the presence of 2.5% high-energy photons causes image deterioration due to increased scatter. To investigate the influence of these photons on image quality, we measured the spectrum of 123I with a medium-energy (ME), a low-energy all-purpose (LEAP) and a low-energy high-resolution (LEHR) collimator. Even in air, using low-energy collimators a high baseline activity was observed over the total energy detection range of the gamma camera. The 159-keV photopeak to scatter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 5 publications
1
43
0
1
Order By: Relevance
“…However, HMR values vary depending on the collimator used, different for low-energy versus medium-energy collimators, but also varying among different low-energy collimator brands. [127][128][129] In part these differences relate to 123 I also emitting multiple low-abundance high-energy ([400 keV) photons, especially a 529-keV emission. While on an intrinsic 123 I spectrum, the higher energy emissions are small in relation to the principle 159-keV peak, a low-energy collimator blocks many of the 159-keV emissions while allowing septal penetration of the higher energy photons that degrade image quality and affect accuracy of quantitative values, such as HMR.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…However, HMR values vary depending on the collimator used, different for low-energy versus medium-energy collimators, but also varying among different low-energy collimator brands. [127][128][129] In part these differences relate to 123 I also emitting multiple low-abundance high-energy ([400 keV) photons, especially a 529-keV emission. While on an intrinsic 123 I spectrum, the higher energy emissions are small in relation to the principle 159-keV peak, a low-energy collimator blocks many of the 159-keV emissions while allowing septal penetration of the higher energy photons that degrade image quality and affect accuracy of quantitative values, such as HMR.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…Septal penetration affects estimation of the H/M ratio in 123 I-MIBG imaging with a low-energy (LE) collimator [17]. Nevertheless, LE collimators are frequently used for imaging 123 I-MIBG [12,18]. Medium-energy (ME) collimators have been shown to provide better quantitative accuracy in 123 I studies [17][18][19].…”
Section: Influence Of Collimationmentioning
confidence: 99%
“…Nevertheless, LE collimators are frequently used for imaging 123 I-MIBG [12,18]. Medium-energy (ME) collimators have been shown to provide better quantitative accuracy in 123 I studies [17][18][19]. Therefore, in order to minimize the effects of septal penetration the ME collimator is preferred.…”
Section: Influence Of Collimationmentioning
confidence: 99%
“…The widespread availability of low-energy (LE) parallel hole collimators determines their common use for 123 I studies; however mediumenergy (ME) collimators have been shown to provide superior semiquantitative accuracy in these type of studies. 3,4 In addition to the major emission of 159-keV photons, 123 I emits high-energy photons of more than 400 keV (approximately 2.87%, main contributor 529 keV, 1.28%), which lead to penetration of the LE collimator septa and cause scatter detected in the 159-keV energy window, resulting in image quality degradation and H/M ratio modification. The H/M ratio is lower when a LE collimator is used because of the increased proportion of mediastinum counts from scattered higher-energy photons.…”
mentioning
confidence: 99%
“…[3][4][5] To further complicate the standardization of the technique, the classification of collimators in two major groups of LE and ME is rather simplistic. Camera vendors offer several types of collimators in order to optimize balance among resolution, sensitivity, and applicable energy range, and collimators with equal designation from different vendors are not exactly the same.…”
mentioning
confidence: 99%